Continuous Technical Guidance for Public Health Center Officer Based on Training Evaluation - Surtimanah, Tuti; Ruhyat, Ejeb; Subekri, Trisno (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2019)
Health promotion services at public health center is essential to support healthy behavior but still many officers did not have the competence and quality to conduct standard health promotion. West Java implemented health promotion training to 238 officers from 10 districts. The research objective was determining changes in participants’ knowledge and its implementation after training as a basis for sustainable technical guidance. Mixed methods design explanatory sequential as results from training analysis and in-depth interviews of officers. The results showed significant change in participants’ knowledge after training by district, no significant difference between districts and education level, and no significant increase in service coverage. Continuous technical direct guidance for officers by district officials and professional organizations is needed to strengthen service management, coordination, partnerships, integration and recording-reporting. Guidance through social media can be considered for use. Further training is needed to strengthen advocacy, partnership, evaluation. Participants were grouped into four as multivariate cluster analysis result of knowledge level after training and education level.